FEATURES OF RELIEF OF UPPER RESPIRATORY TRACT DISEASES INFECTED WITH COVID-19 IN PATIENTS WITH ENDOCRINOLOGICAL DISEASES - Sadullayeva Rushana Sadullayevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Clinical and epidemiological studies conducted during the COVID-19 pandemic prove  the  powerful  negative  impact  of  comorbid  pathology  on  the  severity  and outcomes of SARS-CoV-2 viral infection. Concomitant diseases that are widespread and negatively affect the course of COVID-19 include cardiovascular diseases and diabetes mellitus (DM). The aim of the study was to identify the features of the clinical and metabolic status and disorders of carbohydrate metabolism in hospitalized patients with the new coronavirus infection COVID-19 in combination with type 2 diabetes mellitus as the basis for optimizing glycemia management.